2023
DOI: 10.3390/agriculture13091764
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Potential Distribution of Drosophila suzukii on Madeira Island Using the Maximum Entropy Modeling

Fabrício Lopes Macedo,
Carla Ragonezi,
Fábio Reis
et al.

Abstract: Drosophila suzukii is one of the main pests that attack soft-skinned fruits and cause significant economic damage worldwide. Madeira Island (Portugal) is already affected by this pest. The present work aimed to investigate the potential distribution of D. suzukii on Madeira Island to better understand the limits of its geographical distribution on the island using the Maximum Entropy modeling (MaxEnt). The resultant model provided by MaxEnt was rated as regular discrimination with the area under the curve (AUC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…Determining the potential ranges of these two species could provide useful information for identifying their invasion hotspots. Several case studies have determined their potential ranges in Europe [25][26][27][28]. For example, dos Santos et al (2017) predicted that extreme northern Spain and Portugal [29], France, Austria, Greece, Italy, Switzerland, Albania, and southern Germany comprised invasion hotspots for spotted-winged drosophila; these findings were largely consistent with those of Nair et al (2023) [30].…”
Section: Introductionsupporting
confidence: 67%
“…Determining the potential ranges of these two species could provide useful information for identifying their invasion hotspots. Several case studies have determined their potential ranges in Europe [25][26][27][28]. For example, dos Santos et al (2017) predicted that extreme northern Spain and Portugal [29], France, Austria, Greece, Italy, Switzerland, Albania, and southern Germany comprised invasion hotspots for spotted-winged drosophila; these findings were largely consistent with those of Nair et al (2023) [30].…”
Section: Introductionsupporting
confidence: 67%
“…However, the influences of topographical factors relative to those of climate variables need further investigation. For example, Macedo et al (2023) observed that topographical factors had strong effects on Drosophila suzukii' ranges in Madeira Island in Portugal [33]. In contrast, de Souza et al (2010) [34] and Adeogun et al (2023) [32] did not observe this.…”
Section: Introductionmentioning
confidence: 96%